Quinine-induced bronchiolitis obliterans and organizing pneumonia - Masoodur Rahman; Rayhan Hashmey; Said Abuhasna (Wolters Kluwer Medknow Publications, 2012)
Quinine is a vital anti-malarial drug used in the management of resistant Falciparum malaria. There are previous reports of quinine-induced pulmonary edema and infiltrates. We report the first case of biopsy-proven bronchiolitis obliterans organizing pneumonia (BOOP), confirmed by the Naranjo Adverse Drug Reaction Probability Scale (NADRS) of 5 and a severity scale of 5, secondary to intravenous quinine, in a 15-year-old girl with Plasmodium falciparum infection after a visit to Kenya. Clinical course of the patient followed by review of the literature and appropriate medical interventions for quinine-induced BOOP are suggested.